The Effectiveness of Aloevera Compress on Changes in Breast Swelling of Breastfeeding Women in the Working Area of the Srengat Health Center - Fransiska Septiana; Dwi Lukmawati; Neta Ayu Andera; Ratna Mildawati (Kirana Publisher (KNPub), 2022)
Breast swelling occurs in mothers who have given birth for the first time. Significant breast care can affect the smoothness of breast milk. Breast swelling pain that is not followed up can lead to further complications. Aloevera has many ingredients that are believed to reduce pain and swelling in the breast because it contains aloin and emodin. The purpose of the study was to determine the effectiveness of aloevera compresses against breast swelling of breastfeeding mothers in the work area of the Srengat Health Center. This research method is a pre-experiment with a one group pretest-postest design approach. The population in this study was all postpartum mothers in the working area of the Srengat Health Center. The sampling technique is by taking a large number of samples, which is as many as 22 people. Based on the results of the study, it shows that the value of p = 0.000 (p< 0.05) means that the administration of aloevera compresses is effective against changes in breast swelling in breastfeeding mothers in the work area of the Srengat Health Center Office. The decrease in breast swelling scale after buying aloevera compresses occurs due to the high content of amino acids, minerals, polysaccharides in aloevera which is believed to reduce breast swelling and inflammation. And serves as an anti-inflammatory that localizes both damaged agents and damaged tissues. By doing aloevera compresses on breast swelling, it can reduce swelling in the breast optimally.